2019
DOI: 10.1186/s12870-019-2016-3
|View full text |Cite
|
Sign up to set email alerts
|

Mild water stress-induced priming enhance tolerance to Rosellinia necatrix in susceptible avocado rootstocks

Abstract: BackgroundWhite root rot (WRR) disease caused by Rosellinia necatrix is one of the most important threats affecting avocado orchards in temperate regions. The eradication of WRR is a difficult task and environmentally friendly control methods are needed to lessen its impact. Priming plants with a stressor (biotic or abiotic) can be a strategy to enhance plant defense/tolerance against future stress episodes but, despite the known underlying common mechanisms, few studies use abiotic-priming for improving toler… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 111 publications
2
10
0
Order By: Relevance
“…These changes in SWC were translated into significantly lower values of leaf relative water content (RWC) in mild-WS and severe-WS (89.65% ± 0.81% and 88.37% ± 1.54%, respectively) compared to those of control plants (between 92.25% ± 0.44% and 96.72% ± 0.44%; p < 0.05; Figure 2B), but RWC values did not match stress severity. In contrast to RWC, predawn and midday leaf water potential (Ψ w ) values of water-stressed plants decreased significantly in comparison with control plants (p < 0.05) and accordingly with the soil water depletion (Figure 2C,D), supporting the use of this parameter as an appropriate plant-based water stress indicator in avocado [5,22]. Despite both treatments reaching values of predawn and midday leaf water potential indicative of drought stress [23][24][25], water-stressed plants recovered control values within 5-8 days of rewatering, which possibly indicates the robustness of the water transport system in 'Dusa' plants.…”
Section: Physiological Response To Drought Stress and Rewateringmentioning
confidence: 62%
“…These changes in SWC were translated into significantly lower values of leaf relative water content (RWC) in mild-WS and severe-WS (89.65% ± 0.81% and 88.37% ± 1.54%, respectively) compared to those of control plants (between 92.25% ± 0.44% and 96.72% ± 0.44%; p < 0.05; Figure 2B), but RWC values did not match stress severity. In contrast to RWC, predawn and midday leaf water potential (Ψ w ) values of water-stressed plants decreased significantly in comparison with control plants (p < 0.05) and accordingly with the soil water depletion (Figure 2C,D), supporting the use of this parameter as an appropriate plant-based water stress indicator in avocado [5,22]. Despite both treatments reaching values of predawn and midday leaf water potential indicative of drought stress [23][24][25], water-stressed plants recovered control values within 5-8 days of rewatering, which possibly indicates the robustness of the water transport system in 'Dusa' plants.…”
Section: Physiological Response To Drought Stress and Rewateringmentioning
confidence: 62%
“…Altogether, the above results clearly support that the cacao response to water deficit is strongly governed by stomatal conductance, as the first limiting factor of photosynthetic performance under DS, with the consequent drop in A, as has been previously reported for other cacao genotypes ( De Almeida et al, 2016 ). This is likely to be an early and efficient mechanism encountered in several other tropical perennial crops like mango, coffee or avocado ( Damour et al, 2009 ; Ramalho et al, 2018 ; Tounekti et al, 2018 ; Martínez-Ferri et al, 2019 ), as well as temperate deciduous trees such as peach or apple ( Liu et al, 2012 ; Jiménez et al, 2013 ). However, our results related to chlorophyll fluorescence showed also a reduction in both F v /F m and Y[II] values upon DS in clones that exhibited a lesser tolerance based on water status or gas exchange parameters (i.e., ICS60 and ICS95).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, considering that grafting practice is frequently used to integrate traits of interest between the rootstock and the scion, which in cacao is mainly destinated to confer disease resistance ( Ribeiro et al, 2016 ), and that the rootstock could alter scion responses to various biotic and abiotic factors ( Jiménez et al, 2013 ; Serra et al, 2014 ; Martínez-Ferri et al, 2019 ; Kapazoglou et al, 2021 ), it is possible that the responses observed here could have been influenced by the root-scion interaction. This may have contributed either to certain variability within each clone, due to the genetic variability of the sexually propagated rootstock, or to a more similar behavior between clones, due to the use of the same rootstock.…”
Section: Discussionmentioning
confidence: 99%
“…In avocado, under mild drought stress, the activation of the defence genes Nonexpressor of Pathogenesis-Related Genes 1 (NPR1) and NAC072 reduces infection by the white root rot-causing fungus Rosellinia necatrix. This does not occur under non-stress or severe drought conditions (Martínez-Ferri et al, 2019).…”
Section: Drought Intensitymentioning
confidence: 94%